Thermo-Mechanical Analysis and Process Optimization of Sand Casting for Aluminum Alloy Components: A General Mechanics Study (مجلة العلوم الشاملة, 2026)
This paper presents a professional general-mechanics study of metal casting, with emphasis on gravity sand casting of an aluminum-silicon component. The work combines heat-transfer theory, fluid-flow constraints, feeding mechanics, shrinkage-risk prediction, and mechanical-property estimation into a single analytical-numerical framework. The central objective is to determine how pouring temperature, mold preheat, gate velocity, and riser modulus ratio affect filling time, solidification time, cooling rate, shrinkage porosity, ultimate tensile strength, hardness, and an integrated quality index. The model is intentionally transparent and editable: Chvorinov’s rule is used for solidification scaling, a simplified gating equation is used for filling, a feeding-based shrinkage index is used for porosity risk, and a cooling-rate relation is used to estimate microstructural refinement and strength. A nine-case design matrix is evaluated for a representative Al-Si casting. The results show that raising the riser-to-casting modulus ratio from 1.05 to 1.35 can reduce predicted shrinkage porosity from approximately 5.82% to below 2.20%, while increasing the quality index from about 49.5 to more than 78. The recommended balanced condition is a pouring temperature near 720 degC, mold preheat near 80 degC, riser modulus ratio near 1.35, and moderate gate velocity around 0.35-0.40 m/s. Under this condition, the model predicts shrinkage porosity of about 1.92%, ultimate tensile strength of about 153.6 MPa, and a quality index of 82.4/100. The numerical results are not claimed as experimental measurements; they represent a reproducible engineering case study suitable for design comparison, teaching, and preliminary foundry-process optimization.